Pengaruh Pupuk Kandang Ayam terhadap Pertumbuhan dan Produksi Tanaman Kacang Panjang (Vigna cylindrica L.) - Adnan Mustaqim; Dina Handayani; Nusyirwan Nusyirwan (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to analyze the effect of various doses of chicken manure on the growth and yield of long bean plants (Vigna cylindrica L.). The experimental design used was a Completely Randomized Design (CRD) with four treatments and six replications. Treatments consisted of A (control without fertilizer), B (0.5 kg chicken manure), C (1 kg chicken manure), and D (1.5 kg chicken manure). The variables observed included plant height, number of leaves, number of branches, number of pods, pod length, and fresh pod weight at 14, 28, and 42 Days After Planting (DAP). This study was conducted at the Greenhouse, Department of Biology, State University of Medan. The time of this study was from July to September 2025. The results of the Analysis of Variance (ANOVA) showed that the application of chicken manure had a very significant effect (p<0.05) on all parameters of plant growth and yield. Further DMRT testing results demonstrated that treatment D (1.5 kg of chicken manure) consistently produced the highest yields and significantly differed from the other treatments across all observation phases. It can be concluded that applying 1.5 kg of chicken manure per plot is the optimal dose, significantly increasing vegetative growth and yield of long beans.